Pengaruh Metode Microlearning Berbasis Video Terhadap Kelancaran Komunikasi Siswa Kelas IV pada Pelajaran Bahasa Indonesia SDN Tugusari 04 Bangsalsari Tahun 2025 - Azizah, Berlian Isni; Ulfa, Maria; Rahmawati, Ida (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to determine the influence of the microlearning method on the communication fluency of fourth-grade students in Indonesian language lessons at State Elementary School of Tugusari 04 Bangsalsari, specifically the effect of video-based learning. This study draws on Mayer's cognitive learning theory and multimedia learning theory, which emphasize the importance of conveying information through visual and auditory channels simultaneously. Furthermore, constructivist theory also underpins the approach, encouraging students to construct knowledge through active learning experiences. This study employed a quantitative approach with a descriptive design, using a one-group pretest-posttest design. The research sample consisted of 25 fourth-grade students from State Elementary School Tugusari 04. The instruments used included tests, observations, interviews, and documentation. Data analysis was carried out using normality tests, one-sample t-tests (one-sample t-test), and effect size analysis.